Kuliner Gudeg sebagai Bahan Ajar Bahasa Indonesia bagi Penutur Asing dalam Mendukung Internasionalisasi Bahasa Indonesia - Rama Aji Dananto; Syahla Ayu Yasinta; Syifa Rahmi Fauzani; Vania Salsabila; Kundharu Saddono (Sintaksis : Publikasi Para ahli Bahasa dan Sastra Inggris, 2023)
This research explores the culinary potential of "Gudeg" as a teaching material for Indonesian for Speakers of Other Languages (BIPA) with a focus on supporting the internationalization of Indonesian. Gudeg, a traditional dish from Yogyakarta, is not only a delicacy, but also a means to deepen language and cultural learning experiences. Through qualitative analysis, this study reveals that the integration of Gudeg in the BIPA curriculum can increase participant engagement, deepen understanding of the cultural context, and stimulate interest in the Indonesian language. The results show that culinary elements are not only a source of deliciousness, but also an effective bridge between language and culture. This research contributes to the development of the BIPA curriculum by providing creative and engaging learning approaches. The findings can serve as a guideline for BIPA teachers, educational institutions, and related parties to develop learning strategies that are in line with the trend of internationalization of Indonesian. Gudeg, apart from being a typical dish, emerges as a profound and relevant learning tool, strengthening the role of BIPA programs in supporting the internationalization of Indonesian.